“Hi my friend, give me a hug”: Affective, ethnic-racial and gender intertwining in social relations in a context of early childhood education - Agostinho, Lucilene Morais; Buss-Simão, Márcia (Aprender, 2024)
This article brings together data from a master's degree research, carried out in a public Municipal Early Childhood Education institution in Brazil, with 14 boys and 11 girls aged between 4 and 5 years old. Of these, ten children are white, eight are brown and seven are black. From an Ethnographic Case Study in Education, data was gathered through participant observation of everyday life. The field diary was the main resource in the recording, used with the intention of reporting significant moments and actions, with photographic and audiovisual records also being used to support the observation. Among the data from field records, three dimensions emerged in the social relationships established between children: affective, ethnic-racial, and gender relationships. The analysis of the selected records seek to highlight the reality in/of affective relationships and how they intertwine with ethnic-racial and gender relations, highlighting their relational plots in the personal and social constitution of girls and boys. Through the constructed and shared affections, significant experiences were witnessed that went beyond the barriers of prejudice in valuing ethnic-racial and gender differences.
Keywords: early childhood education; social relationships; affections; children's perspective